2020
DOI: 10.34117/bjdv6n1-221
|View full text |Cite
|
Sign up to set email alerts
|

Expedition on the Lower São Francisco: An X-ray of fisheries and agriculture, pollution, silting and saline intrusion

Abstract: The São Francisco River represents 2/3 of the Northeast Region freshwater availability. Its basin is divided into Upper São Francisco, Middle São Francisco, Sub-Middle São Francisco, and Lower São Francisco. The Lower São Francisco is one of the most impacted regions of the Northeast, considering factors related to fishing, electric power generation and city sewage pollution. The first Scientific Expedition of the Lower São Francisco aimed at evaluating the water quality, pollution, silting, deforestation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Among the marine species, the authors highlighted the robalos and carapebas. In our survey, fishers mentioned all these species, especially robalo and carapeba, as the most prominent occurrences in addition to the xira, which currently is uncommon (Soares et al 2016;Soares et al 2020c). Soares et al (2011; and Rodrigues et al, (2017) also reported that robalos and carapebas were among the most captured species around Penedo and Igreja Nova, 40 km from the São Francisco mouth, corroborating the perceptions of artisanal fishers.…”
Section: Fishing Activity and Fisher Perceptions Of Species Dynamicsmentioning
confidence: 78%
See 3 more Smart Citations
“…Among the marine species, the authors highlighted the robalos and carapebas. In our survey, fishers mentioned all these species, especially robalo and carapeba, as the most prominent occurrences in addition to the xira, which currently is uncommon (Soares et al 2016;Soares et al 2020c). Soares et al (2011; and Rodrigues et al, (2017) also reported that robalos and carapebas were among the most captured species around Penedo and Igreja Nova, 40 km from the São Francisco mouth, corroborating the perceptions of artisanal fishers.…”
Section: Fishing Activity and Fisher Perceptions Of Species Dynamicsmentioning
confidence: 78%
“…Soares et al (2011; and Rodrigues et al, (2017) also reported that robalos and carapebas were among the most captured species around Penedo and Igreja Nova, 40 km from the São Francisco mouth, corroborating the perceptions of artisanal fishers. Soares et al (2020b;2020c) noted an impoverishment of native and freshwater species in fishers catches in the years 2018 and 2019, during which they report the disappearance of xiras, pilombetas (Anchoviella sp., Lophiosilurus alexandrii), and pacamãs and piabas (Astyanax sp. )…”
Section: Fishing Activity and Fisher Perceptions Of Species Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations